Sarah Bassett (ed.), The Cambridge Companion to Constantinople (Cambridge Companion to the Ancient World). - Dark , Ken (Journal of Greek Archaeology, 2024)
The city of Constantinople, which played a central role in the eastern Mediterranean as the capital of the Byzantine empire, has been the subject of very many scholarly studies from the sixteenth century onwards, and this has generated a vast number of books, papers and other contributions in many languages. Thus, compiling a synthesis of this massive body of work is a daunting task, but is here attempted by bringing together 20 historians, art historians and archaeologists to give a thematically structured overview of current knowledge.